Use of fondaparinux in patients with heparin-induced thrombocytopenia on veno-venous extracorporeal membrane oxygenation: A three-patient case series report - Rychlíčková, Jitka; Šrámek, Vladimír; Suk, Pavel (Frontiers in Medicine, 2023)
Heparin-induced thrombocytopenia is a life-threatening immune-mediated complication of unfractionated heparin therapy. Fondaparinux is a therapeutic alternative, but it has limited evidence for its use in patients on extracorporeal membrane oxygenation (ECMO). We present a series of three adult patients with COVID-19 on ECMO who were diagnosed with heparin-induced thrombocytopenia after 7-12 days of unfractionated heparin treatment and were switched to fondaparinux. Fondaparinux was initiated with an intravenous loading dose of 5 mg, followed by a dose of 2.5 mg subcutaneously every 8-12 hours. Dosage was adjusted according to daily measured anti-Xa concentration with a target range of 0.4-0.7 mg/L. The total duration of treatment with fondaparinux and ECMO ranged from 13 to 26 days. One major bleeding episode unrelated to fondaparinux therapy was observed, and the transfusions requirement was also low in all patients. The ECMO circuit was changed once in each patient. This series provides a deep insight into the use of fondaparinux over an extended period of time in patients on ECMO. Based on the presented data, fondaparinux can be considered a reasonable and affordable anticoagulant in patients without a high risk of bleeding.